Regulated assembly of tight junctions by protein kinase C. - Stuart, R O (1995)
We have previously shown that protein phosphorylation plays an important role in the sorting and assembly of tight junctions. We have now examined in detail the role of protein kinases in intercellular junction biogenesis by using a combination of highly specific and broad-spectrum inhibitors that act by independent mechanisms. Our data indicate that protein kinase C (PKC) is required for the proper assembly of tight junctions. Low concentrations of the specific inhibitor of PKC, calphostin C, markedly inhibited development of transepithelial electrical resistance, a functional measure of tight-junction biogenesis. The effect of PKC inhibitors on the development of tight junctions, as measured by resistance, was paralleled by a delay in the sorting of the tight-junction protein, zona occludens 1 (ZO-1), to the tight junction. The assembly of desmosomes and the adherens junction were not detectably affected, as determined by immunocytochemical analysis. In addition, ZO-1 was phosphorylated subsequent to the initiation of cell-cell contact, and treatment with calphostin C prevented approximately 85% of the phosphorylation increase. Furthermore, in vitro measurements indicate that ZO-1 may be a direct target of PKC. Moreover, membrane-associated PKC activity more than doubled during junction assembly, and immunocytochemical analysis revealed a pool of PKC zeta that appeared to colocalize with ZO-1 at the tight junction. A preformed complex containing ZO-1, ZO-2, p130, as well as 330- and 65-kDa phosphoproteins was detected by coimmunoprecipitation in both the presence and absence of cell-cell contact. Identity of the 330- and 65-kDa phosphoproteins remains to be determined, but the 65-kDa protein may be occludin. The mass of this complex and the incorporation of ZO-1 into the Triton X-100-insoluble cytoskeleton were not PKC dependent.